2014
DOI: 10.1039/c3cp53757a
|View full text |Cite
|
Sign up to set email alerts
|

From ultrafast events to equilibrium – uncovering the unusual dynamics of ESIPT reaction: the case of dually fluorescent diethyl-2,5-(dibenzoxazolyl)-hydroquinone

Abstract: The excited state intramolecular proton transfer (ESIPT) reaction of the dually fluorescent 2,5-diethyl-(dibenzoxazolyl)-hydroquinone (DE-BBHQ) was studied with several time resolved techniques. The complementary character of up-conversion and time correlated single photon counting methods was demonstrated. According to the up-conversion experiments, the primary excited dienol form transforms into the monoketo tautomer in a very efficient ultrafast (∼100 fs) proton transfer reaction. The reverse process of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
3
45
2
Order By: Relevance
“…The major time decay is solvent‐dependent and can be clearly ascribed to the cis ‐keto* emission. On the contrary, the minor contribution is only slightly affected by solvent polarity and could thus be tentatively attributed to the emission of a relaxed enol* form or a twisted cis ‐keto* form with a lower radiative rate constant 40…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The major time decay is solvent‐dependent and can be clearly ascribed to the cis ‐keto* emission. On the contrary, the minor contribution is only slightly affected by solvent polarity and could thus be tentatively attributed to the emission of a relaxed enol* form or a twisted cis ‐keto* form with a lower radiative rate constant 40…”
Section: Resultsmentioning
confidence: 98%
“…On the contrary, the minor contribution is only slightly affected by solvent polarity and could thus be tentatively attributed to the emission of a relaxed enol* form or a twisted cis-keto* form with a lower radiative rate constant. [40] Finally, the 6p electrocyclization of 1 a to 1 b in toluene leads to an important photo-modulation of the fluorescence (ca. 80 %), as shown in Figure 5.…”
Section: Photochromic and Fluorescence Properties Of 1 A And 2 Amentioning
confidence: 99%
“…Studies of HBO in highly basic media (MeOH/KOH, EG/KOH and water pH 13) showed a similar behavior. 12,16,33 To further support our assignment, we recorded the fluorescence spectrum of HBO in DMF containing KOH (2 mg of KOH in 5 ml of DMF) upon excitation at 370 nm. Figure S1 (ESI †) shows a comparison between the emission spectra of HBO in pure DMF and containing KOH.…”
Section: Steady-state Fluorescence Spectramentioning
confidence: 84%
“…More and more spectroscopic techniques have been used to investigate ESIPT reaction in recent years. Even though the enormous volume of endeavor has been dedicated 27 28 29 30 31 32 33 34 35 36 37 38 39 40 , the investigations of ESIPT process still remains immense challenges primarily due to the intrinsic complicated processes of physical and chemical property, such as quantum nature, cleavage and formation of hydrogen bond, the change of the excited-state hydrogen bond, nuclear rearrangement process and so forth.…”
mentioning
confidence: 99%
“…In recent years, a large number of ESIPT reactions literatures discussed the so-called double benzoxazoles containing two protons 34 35 36 37 38 39 40 . The best-known examples, bis-3,6-(2-benzoxazolyl)-pyrocatechol (BBPC) and bis-2, 5-(2-benzoxazolyl)-hydroquinon (BBHQ), are symmetrical system with double intramolecular hydrogen bonds.…”
mentioning
confidence: 99%